2023
DOI: 10.1371/journal.pone.0291006
|View full text |Cite
|
Sign up to set email alerts
|

Severe mental illness and the risk of breast cancer: A two-sample, two-step multivariable Mendelian randomization study

Yongjia Cui,
Wenping Lu,
Tianrui Shao
et al.

Abstract: Background Based on epidemiological reports, severe mental illness (SMI) and breast cancer (BC) risk are linked positively. However, it is susceptible to clinical confounding factors, such as smoking, alcohol consumption, etc. Here, we performed a two-sample, two-step multivariable Mendelian randomization (MR) research to explore how the SMI etiologically influences BC risk and to quantify mediating effects of known modifiable risk factors. Methods Data concerning the single nucleotide polymorphism (SNP)-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…However, whether there is a causal relationship between schizophrenia and tumors remains controversial. Some observational studies have suggested a causal relationship between schizophrenia and tumor risk (5), whereas others have not (6). In addition, the incidence of tumors in patients with schizophrenia differs from that in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether there is a causal relationship between schizophrenia and tumors remains controversial. Some observational studies have suggested a causal relationship between schizophrenia and tumor risk (5), whereas others have not (6). In addition, the incidence of tumors in patients with schizophrenia differs from that in the general population.…”
Section: Introductionmentioning
confidence: 99%